Laporan Praktik Lapangan Pada Kejaksaan Negeri Bantul PROSES PENANGANAN PERKARA TINDAK PIDANA PENCURIAN DENGAN KEKERASAN PUTUSAN NOMOR 65/Pid.B/2013/PN.BTL - , DAVID REDIANTO SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In determining the charges in Attorney, prosecutors should be given appropriate attention to the charges against criminal defendants. Too many cases handled by the prosecutor sometimes in performing their duties (prosecuting) attorney is not infallible, as the defendant did not notice a demanding mitigation should be given to the defendant. Job Pratik is very useful to develop a theory of law students who have obtained in the course for five semesters. Field Work Practice also aims to meet the graduation requirements of the Diploma Programme 3 Vocational School of Law, University of Gadjah Mada and to get a law degree and Associate Expert can also distinguish between theories that have been obtained with the practices in the field, in this case in the District Attorney. Based on the theme, the authors set related issues Handling Process Case Crime Theft with Violence Decision Number 65/Pid.B/2013/PN.BTL the result that the crime of theft has been fully regulated in the Criminal Code, ie ranging from 362 to Article Article 367. Attributed to the Penal Code the crime of theft with violence in violation of Article 365 of the Criminal Code, which states as there are elements that is done with weighting followed by violence or threat of violence, committed by two or more persons with allied, done by climbing or damage, as well as child wear fake his key. However, in the classification of any criminal cases there has been no major actors and actors servants, so that in determining charges against the perpetrator basically berbeda.Dakwaan for the main actors described in Article 55 of the Criminal Code which states that elements of those that do, they are told to do , those who participated, and those who advocate or persuade. Thus it is possible to get the maximum criminal threats. As for the actors maid described in Articles 56 and 57 of the Criminal Code, the maximum principal criminal to crime reduced by one third.